2020
DOI: 10.1007/s11467-020-1021-1
|View full text |Cite
|
Sign up to set email alerts
|

The unique carrier mobility of Janus MoSSe/GaN heterostructures

Abstract: Heterostructure is an effective approach in modulating the physical and chemical behavior of materials. Here, the first-principles calculations were carried out to explore the structural, electronic, and carrier mobility properties of Janus MoSSe/GaN heterostructures. This heterostructure exhibits a superior high carrier mobility of 281.28 cm 2 V -1 s -1 for electron carrier and 3951.2 cm 2 V -1 s -1 for hole carrier. Particularly, the magnitude of the carrier mobility can be further tuned by Janus structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Existing studies in the field indicate that the assembly of vdW heterostuctures can not only change the band gap of the individual components, but also provide unique values of E SBH and interface contact types. It has been observed that by interfacing graphene with different semiconductors, such as in graphene/MoS 2 , [29][30][31] graphene/ phosphorene, 32,33 graphene/BN, 34 and MoSSe/BN 35 heterostructures, different electrical contacts can be engineered. Furthermore, the Schottky barrier height and contact types of these heterostructures can also be tuned by extrinsic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies in the field indicate that the assembly of vdW heterostuctures can not only change the band gap of the individual components, but also provide unique values of E SBH and interface contact types. It has been observed that by interfacing graphene with different semiconductors, such as in graphene/MoS 2 , [29][30][31] graphene/ phosphorene, 32,33 graphene/BN, 34 and MoSSe/BN 35 heterostructures, different electrical contacts can be engineered. Furthermore, the Schottky barrier height and contact types of these heterostructures can also be tuned by extrinsic methods.…”
Section: Introductionmentioning
confidence: 99%
“…59,60 The Janus TMD materials have pronounced carrier mobility ranging from 28 to 606 cm 2 V À1 s À1 . 61,62 Besides, a Janus chromium dichalcogenide was proved to have the ability to separate the photogenerated electrons and holes, and the excited carriers had a lifetime of about 2 ns calculated by the time domain density functional theory. 63 Interestingly, the electronic property of the MoSSe monolayer can be tuned by a tensile strain from direct to indirect bandgap, and the excellent visible-light absorption performance promises its use as a photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Heterostructures of 2D layered WS2 with insulating substrates are of fundamental importance in the electronic and optoelectronic applications [31,32].…”
Section: Introductionmentioning
confidence: 99%